608 Immunodominant listeria epitopes compete with vaccine-directed cd8+ t-cell responses rescued by peptide-MHC stabilizing modifications. (9th November 2020) - Flickinger, John; Singh, Jagmohan; Yarman, Yanki; Carlson, Robert; Waldman, Scott; Snook, Adam
Abstract : Background: The Gram-positive bacterium Listeria monocytogenes (Lm) is a promising vector for cancer immunotherapy due to its ability to directly infect antigen-presenting cells, induce potent CD8+ T-cell immunity, and remodel immunosuppressive tumor microenvironments. 1 Recent clinical trials have demonstrated safety and immunogenicity of Lm-based cancer vaccines in lung, cervical, pancreatic, and other cancers. In colorectal cancer, the transmembrane receptor guanylyl cyclase C (GUCY2C) is an emerging target for immunotherapy. 2 Here, we examined the immunogenicity of a recombinant strain of Listeria monocytogenes secreting GUCY2C (Lm-GUCY2C). Surprisingly, Lm-GUCY2C vaccination induced robust Lm-specific CD8+ T-cell immunity but failed to prime GUCY2C-specific CD8+ T-cell responses. These studies explore the hypothesis that immunodominant Lm antigens suppress primary immunity to subdominant GUCY2C epitopes in Lm-GUCY2C Methods: Lm-GUCY2C expresses the extracellular domain of mouse GUCY2C23-429 downstream of an ActA promoter integrated into the genome of the live, attenuated delta actA delta inlB Lm strain. Altered peptide ligands were designed based on NetMHCpan 4.0 peptide-MHC binding algorithms and similarly cloned into Lm. Peptide-MHC class I complex stability was quantified by FACS-based surface peptide-MHC dissociation on the TAP-deficient cell line, RMA-S H-2Kd. 3 In vivo efficacy studies employed IFNγ-ELISpot quantification of T-cell responses and tumor challenge studies with the CT26 colorectal cancer cell line. Adenovirus expressing GUCY2C was used as a positive control. 2 4 Results: Lm-GUCY2C vaccination of BALB/c mice generated Lm-specific CD8+ T-cell responses but an absence of GUCY2C-specific immunity. Peptide-MHC stability studies revealed poor stability of the dominant GUCY2C254-262 epitope complexed with H-2Kd compared to H-2Kd-restricted Lm epitopes derived from the LLO and p60 Lm antigens. Mutation of the GUCY2C254-262 peptide at critical anchoring residues for binding H-2Kd revealed that the altered peptide ligand with an F255Y mutation significantly improved the stability of the GUCY2C254-262-H-2Kd complex. Similarly, vaccination of mice with recombinant Lm-GUCY2C expressing the altered peptide ligand (Lm-GUCY2CF255Y) restored GUCY2C immunogenicity and antitumor immunity. Conclusions: Immunodominant Lm antigens may interfere with immune responses directed to the vaccine target antigen GUCY2C by competing with GUCY2C epitope for MHC class I binding and presentation. Moreover, use of a substituted GUCY2C -peptide ligand with enhanced peptide-MHC class I stability restored GUCY2C-specific immunity in the context of Lm-GUCY2C, an approach that can be translated to patients. Importantly, these studies also suggest that ongoing Lm-based vaccine development programs targeting a variety of antigens in other cancer types may be similarly limited by the immunodominance of Lm epitopes. Acknowledgements: The authors thank Dr. Peter Lauer for providing the pPL2 integration vector used in cloning Lm-GUCY2C and Dr. Sean Murphy for providing the RMA-S H-2Kd cell line. Ethics Approval: Studies were approved by the Thomas Jefferson University IACUC (Protocol # 01956). References: Flickinger JC, Rodeck U, Snook AE. Listeria monocytogenes as a Vector for Cancer Immunotherapy: Current Understanding and Progress. Vaccines (Basel) 2018;6. doi:10.3390/vaccines6030048. Snook AE, Baybutt TR, Xiang B, Abraham TS, Flickinger JC, Hyslop T, et al. Split tolerance permits safe Ad5-GUCY2C-PADRE vaccine-induced T-cell responses in colon cancer patients. J Immunother Cancer 2019;7:104. doi:10.1186/s40425-019-0576-2. Müllbacher A, Lobigs M, Kos FJ, Langman R. Alloreactive cytotoxic T-cell function, peptide nonspecific. Scand J Immunol 1999;49:563–9. Flickinger J. JC, Singh J, Carlson R, Leong E, Baybutt T, Barton J, et al. Chimeric Ad5.F35 vector evades anti-adenovirus serotype 5 neutralization opposing GUCY2C-targeted antitumor immunity. J Immunother Cancer 2020.